2020
DOI: 10.1177/0308275x20959432
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of wilful blindness: An introduction

Abstract: What are the politics of ignorance in an age of misinformation? How can the concept of ‘wilful blindness’ help us to understand the logics involved? We start the introduction to this special issue by arguing that the intrinsic instability of wilful blindness draws valuable attention to the graded nature of intentionality and perception, and the tensions between them. These features are an essential part of the workings of ignorance, as we illustrate with reference to the shifting intentions of drug couriers, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…While cunning senior consultants were certainly trained in and aware of a host of strategic behaviours that would make them more attractive to clients, they also considered a focus on immediate tasks at hand, on the positive economic potential of the world, and on the manifold options inherent in managerial decision-making to reflect basic common sense. This supports the insight that wilful blindness should be thought of as a spectrum ranging from deliberate unawareness to normalised blindness (Bovensiepen and Pelkmans, 2020).…”
Section: Conclusion: An Interplay Of Ignorancesupporting
confidence: 73%
“…While cunning senior consultants were certainly trained in and aware of a host of strategic behaviours that would make them more attractive to clients, they also considered a focus on immediate tasks at hand, on the positive economic potential of the world, and on the manifold options inherent in managerial decision-making to reflect basic common sense. This supports the insight that wilful blindness should be thought of as a spectrum ranging from deliberate unawareness to normalised blindness (Bovensiepen and Pelkmans, 2020).…”
Section: Conclusion: An Interplay Of Ignorancesupporting
confidence: 73%
“…I approach wilful blindness not as an individual trait but as a corporate asset, a discursive tool in the armoury of corporate political strategy, deployed in order to divert, disarm or realign challenges that threaten their capacity to survive and exploit new frontiers. Here we find wilful blindness not so much 'oiling the wheels of social life' (Bovensiepen and Pelkmans, 2020) as lubricating the workings of corporate life. This corporate myopia is created by a carefully crafted performance of CSR, which brings into focus only those aspects of a carbon-constrained world that are amenable to a company's extractive ambitions, blacking out the rest, while positioning extractive companies as warriors against (rather than purveyors of) climate change.…”
Section: Higher Powersmentioning
confidence: 94%
“…Indeed, both anthropologists and sociologists have demonstrated that, under certain circumstances, ignorance is neither the absence nor the inverse of knowledge. Rather, it is a concerted effort, one that is produced and sustained by people in positions of power, as well as those subject to it, as a way to cope, deceive others, avoid conflicts, preserve peaceful relationships, and maintain the status quo (Babidge 2018; Benson and Kirsch 2010; Bovensiepen and Pelkmans 2020; McGoey 2012; Proctor and Schiebinger 2008). Therefore, to understand the sociocultural production of ignorance, “one would have to investigate not gaps in knowledge—which is where most existing studies of ignorance have concentrated their efforts—but rather the production, out of the infinite sea of things that people happen not to know, of culturally recognized .…”
Section: Figurementioning
confidence: 99%